2021
DOI: 10.1080/03079457.2021.1929833
|View full text |Cite
|
Sign up to set email alerts
|

First report of field cases of Y280-like LPAI H9N2 strains in South Korean poultry farms: pathological findings and genetic characterization

Abstract: H9N2 low-pathogenic avian influenza (LPAI) viruses have long been circulating in the world poultry industry, resulting in substantial economic losses. In addition to bird health consequences, viruses from specific lineages such as G1 and Y280 are also known to have the potential to cause a pandemic within the human population. In South Korea, after introducing inactivated H9N2 vaccines in 2007, there were no field outbreaks of H9N2 LPAI since 2009. However, in June 2020, an H9N2 virus was isolated from an outb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Pathology macroscopic findings in our study showed various lesions, such as severe tracheitis with tracheal plug, peritonitis, oophoritis with a specific feature of "broccoli," and a white-yellowish spot in the oviduct. This finding is similar to the report of H9N2 infection in layer farms that exhibited tracheitis with caseous plug (Javeen et al 2019;Lai et al 2021). A white to yellowish exudate found in the oviduct and oophoritis with broccoli feature was considered specific lesions that have never been reported in any case the drop of egg production in poultry farms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Pathology macroscopic findings in our study showed various lesions, such as severe tracheitis with tracheal plug, peritonitis, oophoritis with a specific feature of "broccoli," and a white-yellowish spot in the oviduct. This finding is similar to the report of H9N2 infection in layer farms that exhibited tracheitis with caseous plug (Javeen et al 2019;Lai et al 2021). A white to yellowish exudate found in the oviduct and oophoritis with broccoli feature was considered specific lesions that have never been reported in any case the drop of egg production in poultry farms.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical presentation in the layer commercial farm with decline production sharply in this study is relevant to published data. Lai et al (2021) reported that field cases of LPAI H9N2 strain in layer farms in South Korea showed clinical signs of a respiratory disorder, such as sneezing and gasping, accompanied by egg reduction of over 20%. Several reports confirmed that the AI H9N2 infection did not show apparent clinical symptoms but reduced egg production by 30% (Aamir et al 2007) and up to 80% (El-Houadfi et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although H9N2 AIV is classified as a low pathogenicity virus in poultry, it is causing economic damage to the poultry industry by the decrease in spawning and some mortality rates in commercial chickens. Most chickens infected with H9N2 AIV at farms showed typical signs of influenza, such as respiratory symptoms, egg drop, and mortality (0% to 40%) (summarized in Table 1 ) [ 2 5 61 62 ]. On the other hand, experimental infections in specific-pathogen-free chickens showed no mortality and only mild symptoms, such as depression and decreased feed intake [ 5 19 63 64 65 66 ].…”
Section: Pathogenic Characteristics Of H9n2 Aiv In Chickens and Ducksmentioning
confidence: 99%
“…Initially, vaccination reduced the incidence of infection by Y439 lineage H9N2 viruses; indeed, viruses were isolated mainly to unvaccinated live bird markets or from Korean native chickens [ 4 , 22 ]. Although the virus has not been isolated since June 2018, a Y280 lineage H9N2 virus that is distinct from the previously endemic virus has been circulating in Korea since June 2020 [ 23 , 24 ]. In particular, Y439 lineage H9N2 virus is known to replicate preferentially in the gastrointestinal tract, whereas Y280 lineage H9N2 viruses replicate mostly in the respiratory tract and spread rapidly under laboratory-controlled conditions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Y439 lineage H9N2 virus is known to replicate preferentially in the gastrointestinal tract, whereas Y280 lineage H9N2 viruses replicate mostly in the respiratory tract and spread rapidly under laboratory-controlled conditions [ 25 ]. In one study, they showed mortality with 15 birds dying in 1 day and reducing egg production from 10 to 27% in the field [ 24 ]. Hence, a recombinant vaccine candidate against Y280 lineage virus (rgHS314) was developed in Korea [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%